Entrepreneurs' Well-Being: A Bibliometric Review - Sánchez-García, José Carlos; Vargas-Morúa, Gioconda; Hernández-Sánchez, Brizeida Raquel (Frontiers in Psychology, 2018)
This document aims to summarize and classify existing research on the well-being associated with entrepreneurs through a bibliometric and systematic review of the literature. Its main objectives are: to identify the different theoretical perspectives and research strands that characterize and define the literature on entrepreneurs’ well-being, and highlight the connections between them; and to look for emerging trends and gaps in the literature by comparing the most recent works with those that represent the core of the field. The document is based on bibliometric data: it uses citation techniques to select, analyze, and interpret citation patterns within the literature on entrepreneurs’ well-being. The paper identifies four main groups, as well as several specific research flows and common themes, that represent academic publications on entrepreneurs’ well-being. The research strands on the topic are grouped into four different theoretical perspectives grounded in entrepreneurship related to: culture and innovation in small companies; capital and social aspects; gender and women; and self-employment. Data from the most recent publications are used to verify the original topics and themes seen in the contemporary debate, and to examine how these are discussed. Inevitably, the research findings depend on the design of the research, the databases used, and the bibliometric methods applied. From a practical perspective, the research is expected to impact the construction of theories, management decision making, and teaching. This study describes the remarkable development of the literature on entrepreneurs’ well-being, and the underlying structure of the different streams of research therein. To the best of the authors’ knowledge, this study is the first to identify correlations between Social Science Citation Index and Scopus (Elsevier) databases.